Absolute luminosity measurements with the LHCb detector at the LHC - Collaboration, TL; Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; Cartelle, P; et al. (2011)
Absolute luminosity measurements are of general interest for colliding-beam experiments at storage rings. These measurements are necessary to determine the absolute cross-sections of reaction processes and are valuable to quantify the performance of the accelerator. Using data taken in 2010, LHCb has applied two methods to determine the absolute scale of its luminosity measurements for proton-proton collisions at the LHC with a centre-of-mass energy of 7 TeV. In addition to the classic "van der Meer scan" method a novel technique has been developed which makes use of direct imaging of the individual beams using beam-gas and beam-beam interactions. This beam imaging method is made possible by the high resolution of the LHCb vertex detector and the close proximity of the detector to the beams, and allows beam parameters such as positions, angles and widths to be determined. The results of the two methods have comparable precision and are in good agreement. Combining the two methods, an overall precision of 3.5% in the absolute luminosity determination is reached. The techniques used to transport the absolute luminosity calibration to the full 2010 data-taking period are presented.